Displacement Calculation Method on Front Wall of Covered Sheet-Pile Wharf. (24th December 2018) - Gong, Wen-xue; Wang, Li-yan; Li, Jinsong; Wang, Bing-hui
Abstract : Covered sheet-pile wharves are widely used in port engineering, water conservancy, and civil engineering. This paper is based on the theory of earth pressure and the soil arching effect. According to the stress and deformation characteristics of the covered sheet-pile wharf, the formulas used to calculate the force and deformation of the front wall of a covered sheet-pile wharf under static loads are deduced. The accuracy of the theoretical derivation is verified by comparing actual measured stress and deformation data of Jingtang Port 32#. The comparison shows that when calculating the displacement of the section below the mud surface boundary, the results are in agreement with the in situ data. However, when calculating the displacement of the section above the mud surface boundary, if the anchorage point displacement is ignored because the anchorage point displacement is limited artificially, the calculated tension of the tie rod is relatively large. This leads to a significant decrease in the calculation result of the section above the mud surface boundary, which is very different from actual in situ measurement results. If anchorage point displacement is considered, the calculated tension of the tie rod is more accurate, and the calculation results of the front wall displacement are very close to in situ measurement results because the anchorage point displacement is assumed scientifically.